Influencia del taller SUMAKLANGUAGE en el aprendizaje cognitivo dimensiones: análisis, síntesis y memoria del idioma Awajún en los estudiantes de la Escuela Académico Profesional de Idiomas de la UNSM-2012 - Hervias Coba, Ana Vanesa (2012)
The title of the following investigation is a influence of the workshop SUMAKLANGUAGE which concerns cognitive learning in areas of; Synthesis, Memory and Analysis dimensions, of the language Awajún in the students at the Academic Professional School of Languages of the NUSM-2012. The overall goal of this research was: Meet the grammatical structure of the Awajún language by applying many language techniques. And the specific objectives were: to demonstrates experimentally the students of the Academic Professional School of Language can analyze, synthesize and memorizing the grammar structures of Awajún language, test the effectiveness of the workshop SUMAKLANGUAGE and analyze the influence of the workshop on cognitive learning SUMAKLANGUAGE dimensions Analysis, synthesis and memory of the Awajún language of students at the Academic Professional School of Language of NUSM-2012. The experiment has the following hypothesis ( Hi): The SUMAKLANGUAGE workshop significantly influences on the cognitive learning dimensions of analysis, synthesis and memory of the Awajún language in Students of the Academic Professional School of Languages. To provide a compare and contrast with the hypothesis, research was developed and applied, in the form of an experimental Pre- Test and Post- Test with the subject group of 28 students at the Academic Professional School of languages of the UNSM-2012. The rnethodological structure of the SUMAKLANGUAGE workshop consisted of three stages: Energize, Training and Produce which can be observed in each of the eight topics developed in the investigation. The workshop content was selected according to the interests. The analyze and interpretation of the results of the experimentation of the SUMAKLANGUAGE workshop permitted the establishment of the following statements: the SUMAKLANGUAGE program significantly influenced the cognitive learning in its dimensions of analysis, synthesis and memory in the students at the Academic Professional School of Language of the NUSM-2012.